Strengthening Students’ English Competence Based on the Results of Their English Proficiency Test with the Use of the Expert System with Forward Chaining Method - Putri, Liza Amalia; Nurrahmi, Herly; Chu, Xirui (International Journal of Culture and Art Studies, 2023)
This article presents the results of a study that aimed to strengthen students' English language competency based on the results of their English proficiency tests using an expert system with a forward chaining method. The study employed a quasi-experimental design, with an experimental group receiving intervention using the expert system and a control group following traditional classroom instruction. The analysis of pre and post-test assessments revealed significant improvements in language skills for the experimental group compared to the control group. Additionally, the comparison of English proficiency test results showed higher mean scores for the experimental group, indicating a positive impact of the expert system intervention. The findings highlight the potential of the expert system with forward chaining in providing personalized and adaptive learning experiences, supporting language educators in addressing individual students' weaknesses, and enhancing overall language development. Further research with larger sample sizes and diverse participant groups is recommended to validate these findings and explore the scalability of this approach in language education.